2019
DOI: 10.1158/1078-0432.ccr-18-1897
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of KIT Mutations Are Associated with Differential Clinical Outcomes and Response to Targeted Therapeutics in CBF Acute Myeloid Leukemia

Abstract: Purpose: KIT mutations (KIT þ) are common in core binding factor (CBF) AML and have been associated with varying prognostic significance. We sought to define the functional and clinical significance of distinct KIT mutations in CBF pediatric AML. Experimental Design: Following transfection of exon 17 (E17) and exon 8 (E8) mutations into HEK293 and Ba/F3 cells, KIT phosphorylation, cytokine-independent growth, and response to tyrosine kinase inhibitors (TKI) were evaluated. Clinical outcomes of patients treated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 65 publications
9
50
1
Order By: Relevance
“…KIT mutations have been found in approximately 30% of CBF-AML patients who have chromosome aberrations [3133]. Recent studies showed that active KIT mutations are correlated with a poor prognosis in AML patients [31, 32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KIT mutations have been found in approximately 30% of CBF-AML patients who have chromosome aberrations [3133]. Recent studies showed that active KIT mutations are correlated with a poor prognosis in AML patients [31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that active KIT mutations are correlated with a poor prognosis in AML patients [31, 32]. The major activating KIT mutations are found at D816 and N822 (26 cases and 14 cases in 63 KIT mutation-positive patients, respectively) [33]. Although spatio-temporal analyses of KIT D816V signals have been performed [24, 25, 28], it is unclear whether the N822K mutation in leukemia affects KIT localization and the signal platform.…”
Section: Introductionmentioning
confidence: 99%
“…Of the KITmuts, the codon change D816 was more associated with the significant difference in response than was N822 in t(8; 21) AML, a finding that is supported by in vitro studies demonstrating a positive association of the D816 mutation with stronger KIT phosphorylation and subsequent signalling activation 26,27 . In clinical practice, sequencing results are often not available fast enough, making the development of approaches that can quickly screen for the existence of KIT-D816 necessary.…”
Section: Discussionmentioning
confidence: 74%
“…iii) Post-remission high-dose Ara-C might still exert its role on residual KITmut clones. iv) Mutations in KIT have also been reported to be frequently lost at disease relapse 27,40 .…”
Section: (Ii)mentioning
confidence: 99%
“…KIT mutations are common in CBFL and have been associated with worse prognosis (shorter disease-free survival, relapse-free survival, event-free survival, overall survival) [147]. A phase III study of gemtuzumab ozogamicin (Mylotarg®; Pfizer/Wyeth-Ayerst Laboratories) showed that GO abrogated the negative prognostic effect of exon 17 (E17) mutations in treated patients [148]. Moreover, the outcome of patients harboring KIT mutations in the Cancer and Leukemia Group B (CALGB) study, appeared not to be worse than that of patients with KIT wild-type after treatment with dasatinib, implying that a potentially adverse impact of KIT mutations might be abrogated in treated patients [144].…”
Section: Molecular Targeted Therapy Of Cbfl: the Progress And Future mentioning
confidence: 99%